The exaptive potential of (object) play behavior. Issue 1 (2nd January 2023) - Leca, Jean-Baptiste; Gunst, Noëlle
ABSTRACT: There are many adaptationist hypotheses and non-selectionist accounts for the evolution of play. Some scholars argued that, 'primary-process play' originally arose as a by-product of fortuitous conditions, adaptive or not (e.g. high metabolic energy, boredom). Once evolved, these basic playful behavioral elements, characterized by some quirkiness, arbitrariness, redundancy, flexibility, and latent potential, may serve as a built-in reservoir of creative and adaptive variability. As such, they could subsequently be co-opted for beneficial or fitness-enhancing behavioral effects (i.e. exaptations Type 2) during further evolutionary transformation into more elaborate secondary-process and tertiary-process play. We built a theoretical case for (object) play as a co-optable behavioral spandrel, with a potential for exaptations Type 2, and proposed a research design to empirical test whether stone play traditions can be exapted into stone tool use in non-human primates. Our approach is consistent with Gould's pluralistic perspective on evolutionary theory.